Lack of Endogenous Annexin A1 Increases Mast Cell Activation and Exacerbates Experimental Atopic Dermatitis - Parisi, Jessica dos Santos; Correa, Mab Pereira [UNESP]; Gil, Cristiane Damas [UNESP] (Mdpi, 2019)
Annexin A1 (AnxA1) is a protein with potent anti-inflammatory actions and an interesting target that has been poorly explored in skin inflammation. This work evaluated the lack of endogenous AnxA1 in the progression of ovalbumin (OVA)-induced atopic dermatitis (AD)-like skin lesions. OVA/Alum-immunized C57BL/6 male wild-type (WT) and AnxA1 null (AnxA1(-/-)) mice were challenged with drops containing OVA on days 11, 14-18 and 21-24. The AnxA1(-/-) AD group exhibited skin with intense erythema, erosion and dryness associated with increased skin thickness compared to the AD WT group. The lack of endogenous AnxA1 also increased IgE relative to WT animals, demonstrating exacerbation of the allergic response. Histological analysis revealed intense eosinophilia and mast-cell activation in AD animals, especially in AnxA1(-/-). Both AD groups increased skin interleukin (IL)-13 levels, while IL-17A was upregulated in AnxA1(-/-) lymph nodes and mast cells. High levels of phosphorylated ERK were detected in keratinocytes from AD groups. However, phospho-ERK levels were higher in the AnxA1(-/-) when compared to the respective control groups. Our results suggest AnxA1 as an important therapeutic target for inflammatory skin diseases.
Keywords: inflammation; mast cell; eosinophil; ERK; immunohistochemistry; skin